Pemanfaatan Media Sosial Sebagai Sarana Komunikasi Guru Kelas Dengan Orang Tua Wali Siswa - Mirza Fazah (THE JOER: Journal Of Education Research, 2022)
The existence of parents and guardians associations and madrasa committees is a forum that must synergize with activities and support all programs that have been established by madrasas for the progress and development of madrasas at the national and regional level. Social media is one of the programs on the latest and latest android mobile communication tools that makes communication services with several parents and guardians of students into a single unit quickly and easily so that any information regarding programs, activities, invitations and student evaluations can be conveyed through social media on nowadays. The results of this study include the use of social media as a medium of communication between class teachers and their parents, the positive and negative impacts of using social media between classroom teachers and their parents, and whatsApp social media is the choice of the parents' guardian group. The conclusion in the study is the positive impact of the use of social media between classroom teachers and parents of grade 1, 2, 3 MI Muh Nogosari Kulon progo students for the 2021/2022 academic year is the ease of obtaining information, the speed of obtaining information and communication, communication can take place continuously. interactive. Meanwhile, the negative impact of the use of social media between classroom teachers and parents of grade 1, 2, 3 MI Muh Nogosari Kulon progo students for the 2021/2022 academic year is that users' concerns are focused on the impact of pornography on the internet, especially on children. with school and education.